Predicting depressive symptoms in employees through life stressors: subgroup analysis by gender, age, working hours, and income level - Moon, Jiwan; An, Yoosuk; Jeon, Sang Won; Cho, Sung Joon (Frontiers in Public Health, 2024)
BackgroundAlthough evidence has accumulated regarding the association between various stressors and depression, few studies have considered the context in which multiple stressors coexist simultaneously. Thus, this study aimed to evaluate the relative importance of seven major life stressors on depressive symptoms: workplace stress, family relationships, interpersonal conflicts, health problems, financial strains, traumatic events, and mannerisms, and analyzed its variation in subgroups.MethodsData from 12,541 Korean employees were analyzed. Sociodemographic data such as gender, age, education, marital status, working hours, and income level were collected from the study participants, and the Center for Epidemiologic Studies Depression Scale (CES-D) was employed to assess depressive symptoms. Additionally, life stressors experienced during the previous month and their severity were investigated via a questionnaire. Multiple regression analysis was performed to assess the independent effects of seven major life stressors on depressive symptoms, while controlling for sociodemographic factors. Subgroup analysis was also conducted to determine whether the effect of stressors varied by gender, age, working hours, and income level.ResultsWorkplace stress (β = 0.411, p < 0.001) had the greatest effect on depressive symptoms, followed by mannerisms (β = 0.191, p < 0.001), family relationships (β = 0.120, p < 0.001), interpersonal conflicts (β = 0.077, p < 0.001), health problems (β = 0.054, p < 0.001), financial strains (β = 0.046, p < 0.001), and traumatic events (β = 0.021, p = 0.002). Moreover, significant variance in the rank order of effects of stressors across gender, age, working hours, and income level was observed, as revealed by subgroup analysis.ConclusionThis study identified the effects of seven major life stressors on depressive symptoms and suggests that the rank order of these effects varies depending on sociodemographic factors. These findings expand the understanding of the complex relationship between concurrent life stressors and depression, and highlight the need for personalized interventions to prevent and manage depression among Korean employees.